2015
DOI: 10.5966/sctm.2015-0043
|View full text |Cite
|
Sign up to set email alerts
|

Oral Mucosal Lamina Propria-Progenitor Cells Exert Antibacterial Properties via the Secretion of Osteoprotegerin and Haptoglobin

Abstract: The oral cavity possesses a diverse microflora, yet recurrent infections within healthy individuals are rare. Wound healing within the buccal mucosa is preferential, potentially because of the presence of oral mucosal lamina propria-progenitor cells (OMLP-PCs). In addition to their multipotency, OMLPPCs demonstrate potent immunosuppressive properties. The present study investigated whether OMLP-PCs possess antibacterial properties, directly interacting with microorganisms and contributing to the maintenance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 37 publications
0
24
2
Order By: Relevance
“…9 OMLP-PCs are also multipotent, 10 immunosuppressive, 11 and anti-bacterial. 12 In recent years, it has been reported that paracrine factors derived from stem cells are the main facilitators in driving tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…9 OMLP-PCs are also multipotent, 10 immunosuppressive, 11 and anti-bacterial. 12 In recent years, it has been reported that paracrine factors derived from stem cells are the main facilitators in driving tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically, this region is constantly exposed to injury, however renewal and healing are very prompt. Oral cavity is easily accessible and displays unique characteristics such as fetal-like wound healing [26] and antibacterial properties [27,28]. The oral cavity has antibacterial properties as a part of the native immunity.…”
Section: Oral Cavity As a Promising Source Of Therapeutic Exosomesmentioning
confidence: 99%
“…Epithelial antimicrobial peptides (β-defensin coming from oral epithelium) have been identified and examined [29]. Also osteoprotegerin and haptoglobin -peptides secreted by progenitor cells of lamina propria, reduce growth of several pathogens [27]. It is easy to notice that wounds appearing in this region are healed much faster than those affecting skin, carrying low risk of scars formation.…”
Section: Oral Cavity As a Promising Source Of Therapeutic Exosomesmentioning
confidence: 99%
“…The oral mucosa is a suitable cell source for tissue engineering and regenerative medicine applications, including cell sheet fabrication. It is easily accessible and exhibits unique characteristics such as foetal‐like wound healing [1] and antibacterial properties [2,3]. While skin wounds generally heal with scar (“reparation”), wounds in the oral mucosa are prone to heal without scar (“regeneration”) [4].…”
Section: Introductionmentioning
confidence: 99%
“…These peptides operate by disrupting the microbe cell membrane [17]. Progenitor cells from the oral mucosal lamina propria similarly secrete the antimicrobial peptides osteoprogetrin and haptoglobin, which, in effect, could reduce the growth of several pathogens [2]. To this end, we evaluated the exosomes impact on growth of Staphylococcus aureus .…”
Section: Introductionmentioning
confidence: 99%